(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay examines the problems connected to the exercise of the right of conscientious objection in the matter of voluntary termination of pregnancy, starting with the two recent decisions of the European Court of Human Rights against Sweden. Taking into account these two decisions and those of the European Committee of Social Rights against Italy, as well as the Italian constitutional principles, the essay focuses on the position of doctors and health professionals who decide to refuse services strictly connected to a freely chosen profession.